DESAIN INFOGRAFIS TENTANG PEKERJAAN TERKAIT UI DAN UX - Prabowo, Dwi Puji; Senoprabowo, Abi; Muslih, Muslih; Khamadi, Khamadi; Rismansa, Alya Tsabitah (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2023)
Abstract: Online marketing carried out by various companies has increased due to the Covid 19 pandemic. Companies create mobile platforms and websites to develop their business online. Thus, the need for work in the field of mobile applications and websites is increasing, especially in the fields of User Interface (UI) and User Experience (UX). A large salary makes people interested in pursuing work in this field. However, jobs in the UI and UX fields are still not well understood by the public, especially regarding career opportunities and what competencies are needed. So, there is a need for socialization media to the public regarding types of work in the UI and UX fields through infographics. Through data collection using documentation and literature study techniques, qualitative data about work related to UI UX is analyzed and becomes an infographic design concept. The infographic design was made using Keleher's (2020) stages, namely ideation, research, copywriting, and design. The result is an infographic design that contains types of work other than UI UX designer, namely UX researcher, UX strategist, UX writer, information architect, visual designer, and interaction designer. Visualization of infographics with character designs with fields of work and accompanied by explanations through copywriting makes it easier for readers to understand the message conveyed. Keywords: Infographics, user interface, user experience, work Abstrak: Kebutuhan perusahaan untuk melakukan pemasaran secara online meningkat akibat pandemi Covid 19. Perusahaan membuat platform mobile dan situs untuk mengembangkan bisnisnya secara online. Sehingga kebutuhan pekerjaan di bidang aplikasi mobile dan situs meningkat khususnya di bidang User Interface (UI) dan User Experience (UX). Gaji yang cukup besar membuat masyarakat tertarik menekuni pekerjaan di bidang ini. Namun, pekerjaan di bidang UI dan UX masih kurang dipahami masyarakat khususnya peluang karir dan kompetensi apa saja yang dibutuhkan. Sehingga perlu adanya media sosialisasi ke masyarakat terkait jenis pekerjaan di bidang UI dan UX melalui infografis. Melalui pengumpulan data dengan teknik dokumentasi dan studi pustaka, maka data kualitatif tentang pekerjaan terkait UI UX dianalisis dan menjadi konsep perancangan infografis. Selanjutnya perancangan infografis menggunakan tahapan Keleher (2020) yaitu ideation, research, copywiting, dan design. Hasilnya adalah perancangan infografis yang berisi jenis pekerjaan selain desainer UI UX yaitu UX researcher, UX strategist, UX writer, information architect, visual designer, dan interaction designer. Visualisasi infografis dengan desain karakter dan interaksinya sesuai bidang pekerjaan serta penjelasan melalui copywriting memudahkan pembaca memahami pesan yang disampaikan. Kata Kunci: infografis, pekerjaan, user interface, user experience